Penegakan Kode Etik Guru dalam Pelaksanaan Tugas Profesi Guru Guna Mewujudkan Sekolah Berbasis Ramah Anak Bagi Guru di Kabupaten Sukoharjo - Budoyo, Sapto; Pratama, Praditya Arcy; Sholihah, Nurul Fatimatus (Jurnal Inovasi Pembelajaran di Sekolah, 2024)
Enforcement of the teacher's code of ethics has a very important role in ensuring that teachers' professional duties are carried out professionally, especially in creating a child-friendly educational environment. This research aims to analyze the enforcement of the teacher code of ethics in Sukoharjo Regency, as well as its impact on creating child-friendly schools. The method used in this research is the Normative Juridical approach. The research results show that although the majority of teachers understand and try to apply the code of ethics in carrying out their duties, there are several challenges in enforcing it, such as limited supervision and differences in understanding of the code of ethics. Teachers who uphold a code of ethics tend to pay attention to students' psychological well-being and implement an educational approach that is inclusive, non-discriminatory and supports children's holistic development. Therefore, more effective enforcement of the code of ethics is needed, supported by continuous training and more intensive supervision to create better child-friendly schools in Sukoharjo Regency.